Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-27091-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of bicistronic expression system for the enhanced and reliable production of recombinant proteins in Leuconostoc citreum

Abstract: The lactic acid bacteria (LAB) Leuconostoc citreum are non-sporulating hetero-fermentative bacteria that play an important role in the fermented food industry. In this study, for the enhanced and reliable production of recombinant proteins in L. citreum, we developed a bicistronic design (BCD) expression system which includes a short leader peptide (1st cistron) followed by target genes (2nd cistron) under the control of a single promoter. Using superfolder green fluorescent protein (sfGFP) as a reporter, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…The strongest three bicistronic promoters shown in our study remained higher potency than the control when expressing different proteins, so we inferred that the forecistron sequence could be developed as an independent expression enhancer. Furthermore more parameters, such as the length [36] and the amino acid composition [37] of the first cistron need to be investigated to evaluate its improvement ability in combination with different promoters, UTR, SD sequences [19,38], target genes, and different hosts-the designing principles established in E.coli may not be fully applicable to C. glutamicum, as the 24 promoters in our study showed a completely different intensity trend between the two hosts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The strongest three bicistronic promoters shown in our study remained higher potency than the control when expressing different proteins, so we inferred that the forecistron sequence could be developed as an independent expression enhancer. Furthermore more parameters, such as the length [36] and the amino acid composition [37] of the first cistron need to be investigated to evaluate its improvement ability in combination with different promoters, UTR, SD sequences [19,38], target genes, and different hosts-the designing principles established in E.coli may not be fully applicable to C. glutamicum, as the 24 promoters in our study showed a completely different intensity trend between the two hosts.…”
Section: Discussionmentioning
confidence: 96%
“…Solutions by optimizing the TIR/UTR sequence for each protein target is very tedious and timeconsuming [18][19][20]. To build a vector with good compatibility of expression of various proteins, a bicistronic design (BCD) expression strategy can be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Jang et al . ). Using the host and its vector series, we further developed a dsrC ‐ mutant strain producing no dextran in sucrose medium (Jin et al .…”
Section: Introductionmentioning
confidence: 97%
“…The minimized shuttle vector showed a broad host spectrum covering various LAB species such as L. mesenteroides, Lactococcus lactis, Lactobacillus plantarum, Lb. reuteri, Streptococcus thermophilus, Weissella confusa and Oenococcus oeni, and thus it has been used to express heterologous genes in several studies Cho et al 2015;Jang et al 2018). Using the host and its vector series, we further developed a dsrCmutant strain producing no dextran in sucrose medium (Jin et al 2014), a foodgrade expression system by employing a bile salt hydrogenase gene (bsh) (Cho et al 2015) and a high-copy number plasmid (pCB4270) system screened using fluorescenceactivated cell sorting (FACS) technique (Son et al 2016).…”
Section: Introductionmentioning
confidence: 99%